ITRAQ-based quantitative proteomic analysis of synergistic antibacterial mechanism of phenyllactic acid and lactic acid against Bacillus cereus. (January 2021) - Ning, Yawei; Fu, Yunan; Hou, Linlin; Ma, Mengge; Wang, Zhixin; Li, Xingfeng; Jia, Yingmin
Graphical abstract: Highlights: PLA is a promising alternative to benzoic acid due to broad antibacterial activity. Combined antibacterial effect of PLA with LA were evaluated. Antibacterial mechanism was explored by iTRAQ-based quantitative proteomic analysis. This study may help in explaining the bio-preservation effect of lactic acid bacteria. This study may provide insights into the application of PLA in food spoilage control. Abstract: Phenyllactic acid (PLA) as a phenolic acid by lactic acid (LA) bacteria shows enhanced antibacterial activity when coexisting with LA, while the antibacterial mechanism of PLA combined with LA was unknown. Hence, the antibacterial mechanism of PLA and LA was investigated against Bacillus cereus . Flow cytometry and TEM analysis demonstrated that single PLA and LA disrupted the membrane integrity and the morphology, while combined PLA and LA synergistically enhanced the damage. iTRAQ-based proteomic analysis suggested that PLA down-regulated kdpB and inhibited K + transport, disturbed the function of ribosome and expression of competence genes; LA down-regulated periplasmic phosphorus-binding proteins and inhibited phosphorus transport, disturbed the function of ribosome, TCA cycle, as well as purine and pyrimidine metabolism; and combined PLA and LA inhibited K + and phosphorus transport, and influenced the synthesis of purine and pyrimidine metabolism. The investigation could provide some insights into the application of PLA in food preservation.